Are orthodontic systematic reviews registered a priori in PROSPERO?. (2nd October 2017) - Sideri, Sofia; Papageorgiou, Spyridon N.; Eliades, Theodore
ABSTRACT: Introduction: Aim of this study was to assess the registration of orthodontic systematic reviews in PROSPERO. Method: Seven databases were searched for orthodontic systematic reviews published in 2012-2016. After duplicate study selection and data extraction, descriptive statistics, followed by chi-square/Fisher exact tests were calculated. Finally, bivariable/multivariable regression with relative risks (RR) and 95% confidence intervals (CIs) was used. Results: A total of 182 orthodontic systematic reviews were identified, 37 (20.3%) of which were registered in PROSPERO, with registration rates ranging from 4.3% in 2012 to 37.0% in 2016. Differences in review registration were found according to publication year, geographic origin, multicentre status, funding, and journal category. After controlling for confounders, each additional year was associated with increased registration probability (RR = 1.51; 95% CI = 1.19–1.93). Reviews from South America were more likely to be registered than reviews from Europe (RR = 1.49; 95% CI = 1.06–2.11). Finally, reviews published in orthodontic specialty journals were more likely to be registered than reviews in general dentistry journals (RR = 1.87; 95% CI = 1.02–3.49). Conclusions: A small percentage of orthodontic systematic reviews was registered a priori, although improvement signs have been seen since the initiation of PROSPERO.